DOES SOCIAL CAPITAL FOCUS DETERMINE USERS’ INTENTIONS TO LIKE, COMMENT AND SHARE LIFESTYLE BRAND-RELATED CONTENT ON SOCIAL MEDIA? - Ciunova-shuleska, Anita; Nikolina Palamidovska-Sterjadovska; Irena Bogoevska-Gavrilova (Faculty of Economics-Skopje, Ss. Cyril and Methodius University in Skopje, 2021)
The purpose of this research is to analyze the differences in users’ intentions to like, comment and share lifestyle brand-related content on social media based on the social capital focus. In this paper, social capital is conceptualized as a positive outcome of users’ interaction on social media, focusing on bonding and bridging dimensions of social capital. However, in order to examine the differences in intentions to like, comment and share between social media users with bridging and bonding focus, social capital is analyzed as a cause of social media engagement, i.e. users’ contribution in terms of liking, commenting and sharing brand-related content on social media. A survey with social media users was carried out, using questionnaires as a method of data collection. A data set of 415 effective responses is collected and ANOVA test was used. The respondents were divided into two groups: social media users with bridging focus and social media users with bonding focus. ANOVA test revealed significant differences in intention to contribute to life-style brand-related content among the social media users with different level of social capital focus. Namely, the results indicated existence of significant differences in intention to like, intention to share and intention to comment lifestyle brand-related content depending on the social media users’ social capital focus. Social media users with bridging focus showed stronger intentions to like, share and comment life-style brand-related content comparing to social media users with bonding focus. The findings of this research study may help social media marketing managers to successfully design and implement effective life-style brand-related content depending on the social capital focus of the users.
Keywords: social media, like, comment, share, life style content, social capital, intentions